Evaluating Institutional Drivers of the Knowledge-Practice Gap: A Mixed-Methods Study on the Transition to Entrepreneurial Practice - Daniel Kurniawan; Damelina Basauli Tambunan (LP2M IAIN Palopo, 2026)
Despite the increasing integration of entrepreneurship into business school curricula, a persistent